Contribution of intertwined loop to membrane association revealed by Zika virus full‐length NS1 structure. (30th August 2016) - Xu, Xiaoying; Song, Hao; Qi, Jianxun; Liu, Yuqian; Wang, Haiyuan; Su, Chao; Shi, Yi; Gao, George F
Abstract: The association of Zika virus (ZIKV) infections with microcephaly and neurological diseases has highlighted an emerging public health concern. Here, we report the crystal structure of the full‐length ZIKV nonstructural protein 1 (NS1), a major host‐interaction molecule that functions in flaviviral replication, pathogenesis, and immune evasion. Of note, a long intertwined loop is observed in the wing domain of ZIKV NS1, and forms a hydrophobic "spike", which can contribute to cellular membrane association. For different flaviviruses, the amino acid sequences of the "spike" are variable but their common characteristic is either hydrophobic or positively charged, which is a beneficial feature for membrane binding. Comparative studies with West Nile and Dengue virus NS1 structures reveal conserved features, but diversified electrostatic characteristics on both inner and outer faces. Our results suggest different mechanisms of flavivirus pathogenesis and should be considered during the development of diagnostic tools. Synopsis: The Zika virus (ZIKV) nonstructural protein 1 (NS1) functions in viral replication, pathogenesis, and immune evasion. Here, we solved the crystal structure of full‐length NS1 protein, and found an extended membrane association interface contributed by the hydrophobic "spike" of a long intertwined loop, providing important information for ZIKV pathogenesis and development of diagnostic tools. Full‐length ZIKV NS1 structure has a similar overall structural fold to other flavivirus NS1 structures. A long intertwined loop forming a hydrophobic "spike" in the NS1 structure could contribute to cellular membrane association. The variable "spike" residues for different flaviviruses have common hydrophobic or positively charged characteristics. ZIKV NS1 has diversified electrostatic characteristics on both inner and outer faces. Conservation analysis of NS1 structure reveals vulnerable sites for the development of diagnostic tools. Abstract : The crystal structure of the Zika virus NS1 protein reveals an extended intertwined loop forming a hydrophobic "spike" that contributes to cellular membrane association.